How does CRM strategy vary across small and large enterprizes? - Das, Tamoghna (2007)
This research examines the strategic aspect of Customer Relationship Management, or CRM. The research commences by evaluating the central role of CRM and incorporates the critical factors of formulating a cross-functional approach to CRM strategy. Reviewing of contemporary literature helps in formulation of the core strategies of CRM which emphasise on process based approach and work flow management due to integration of these processes. The research also compares this cross-functional framework to examine how different it is between small and large enterprises through adopting a case study approach. The literature review, analysis and findings help realize the importance of processes and business process management in CRM. It also helps understand that how critical this would be to apply a perfect work flow through the processes in a CRM system. At the same time the research limitations are mentioned. It then recommends a CRM strategic model that encapsulates both CRM strategy and implementation factors. The model comes up with eight key processes and four key elements. Further due to limitations the research ends with proposal of examining the strategic model and further research areas.